Multiscale characterization and velocity-related risk zoning of impact damage in mature broccoli under controlled single-impact simulation - Liming Qin; Meiling Yuan; Zheng Xu; Jiajun Wu; Jingbin Li (Postharvest Biology and Technology, 2026)

A double-platform assay for rapid and on-site detection of chikungunya virus by integrating catalytic hairpin assembly with lateral flow immunochromatography assay - Ruijie Lu; Dawen Chen; Ai Chen; Shuo Ma; Yuming Yao; Yaya Chen; Gulinaizhaer Abudushalamu; Meiling Zhou; Xiao Li; Yue Zheng; Wenjing Lu; Yueqi Wang; et al. (Analytica Chimica Acta, 2026)

Forecasting transportation decarbonization pathways and deciphering structural moderating mechanisms in in-situ urbanization: An interpretable machine learning and multi-scenario assessment framework - Lu Chen; Wei Liu; Meiling Wu; Jingyi Zhao; Fanjie Luo (Environmental Impact Assessment Review, 2026)

Landsat observation reveals upward trend of surface water temperature in the Three Gorges Reservoir over the past quarter century: divergent effects of climate changes and dam constructions - Han Peng; Botian Zhou; Dongmin Wang; Yue Yuan; Guang Li; Meiling Liu; Ling Wu; Mingsheng Shang (Journal of Oceanology and Limnology, 2026)

Uncovering the synergistic effects of digital–intelligent transformation and industrial structure upgrading on eco-efficiency:Evidence from 284 Chinese cities - Meiling Wu; Wei Liu; Rongguang Zhang; Yuying Yue (Journal of Cleaner Production, 2026)

TRPV4/IP3R-1-mediated endothelial pyroptosis drives pulmonary microvascular endothelial permeability in endotoxin-induced acute lung injury - Shasha Liu; Shuan Dong; Lirong Gong; Jing Yang; Huayang Liu; Meiling Piao; Ya Wu; Huirong An; Li Zhang; Jianbo Yu (Inflammation Research, 2026)

Spatiotemporal cube for identifying Cd-dominated heavy metal stress in rice using signal decomposition and hotspot analysis from GF-6 time series images - Yanan Wen; Tianyi Wang; Meiling Liu; Hui Zhang; Yuxin Zhao; Ben Yang; Xutao Yan; Ling Wu (International Journal of Remote Sensing, 2026)

Bionic construction and performance assessment of 3D bioprinted small-diameter artificial blood vessels - Yuan-Zhu Xin; Wenyu Jin; Qianqian Wu; JunHee Lee; Geng Li; Yan Chen; Jun Liu; Seok-Jo Yang; Jiazi Gao; Meiling Quan; Zhenning Liu (Chemical Engineering Journal, 2026)

Seamless 1-km hourly land surface temperature estimation via multi-source data integration and automated machine learning - Yumin Li; Meiling Gao; Zhenhong Li; Penghai Wu; Bin Wang; Rongtang Xu; Guijun Yang (Urban Climate, 2026)

Co-exposure to PS-NPs and HFPO-TA potentiates reproductive toxicity via ferroptosis and SLC1A5-Mediated glutamine deprivation in male mice - Lihai Wu; Jing Ding; Jiayu Xue; Meiling Le; Yiqi Wan; Wanting Zhao; Yangyang Yuan; Xiaodong Kuang; Xinyuan zhao; Liping Zheng; Dalei Zhang (Chemico-Biological Interactions, 2026)

Impacts of vegetation management on pollination network structure and robustness in urban parks: A case study from Beijing Wenyu River Park - Yaxuan Li; Meiling Shu; Chenxi Li; Liwen Liu; Yan Zhou; Lan Wu; Yuyu Wang (Urban Ecosystems, 2026)

SEMA4A promotes acute myeloid leukemia progression through inhibiting apoptosis - Xinyu Li; Binyu Yao; Meiling Sun; Wangshi Li; Xingzhi Lv; Keyang Luo; Yue Wu; Ruolin Xiu; Yuzhu Ma; Fukai Liu; Yanhong Zhao; Shengjin Fan; et al. (Genes & Genomics, 2026)

Decoupling predictors of arbuscular mycorrhizal fungal α- and β-diversity: Plant phylogeny versus functional traits in an alpine artificial grassland of Three-River Source Region - Guoxi Shi; Yingli Ma; Ning Wu; Meiling Guo; Xinchuang Wang; Yongjun Liu; Huyuan Feng; Huakun Zhou; Buqing Yao (Applied Soil Ecology, 2026)

Hydrangea-derived nitrogen-doped carbon dots: A dual-purpose platform for on-site chlortetracycline detection and time-limited anti-counterfeiting - Meiling Long; Decheng Peng; Jun Yang; Shaogui Wu (Analytica Chimica Acta, 2026)

Mutual reinforcement of economic and social exchanges between new farmers and rural communities in China: Implications for alternative agriculture development - Meiling Wu; Shengxi Xin (Journal of Rural Studies, 2026)

Effects of different dark septate endophyte species on growth, Pb tolerance and associated physiological responses in Astragalus membranaceus under Pb stress - Gen Li; Meiling Wu; Qingqing Liu; Yashuo Tian; Simiao Wang; Yibang Zhang; Qing Dang; Fei Cao; Li Han (Plant and Soil, 2026)

Bidirectional gut-heart axis interactions in the context of predictive, preventive, and personalised medicine: a time-course analysis of comorbidity and mortality risk in a large population cohort - Meiling Cao; Di Liu; Haotian Wang; Cancan Li; Huapeng Lin; Lijuan Wu; Youxin Wang (EPMA Journal, 2026)

Spatiotemporal Profiling of Intratumoral Free Payload Distribution via MALDI Imaging Mass Spectrometry: Implications for Drug-to-Antibody Ratio Optimization in Antibody–Drug Conjugates - Tingting Cai; Ziyi Li; Qiaofang Yan; Guangcun Huang; Kaiying Jia; Xiaotong Chen; Junling Dun; Jinghua Zou; Meiling Tan; Yue Wu; Fan Wang (The AAPS Journal, 2026)

Bridging data gaps in landslide early warning: Physics-derived rainfall thresholds under rainfall uncertainty - Hao Zou; Weiye Huang; Ting Liu; Henghao Cai; Shuai Mao; Bing Chen; Meiling Wu; Qingyu Zhang; Xiao Liu; Shu Zhang (Engineering Geology, 2026)

Enhanced electrocatalytic degradation of concentrated simulated metronidazole wastewater by MIL-101(FeCu)/graphite felt electrodes - Songshan Jiang; Fan Wu; Rui Wen; Lin Xu; Qian Zhong; Meiling Yang; Bai He; Huan Yi; Huan Pang (Chemical Engineering Journal, 2026)

Pore Structure Characteristics and Controlling Factors of Different Lithofacies in Lacustrine Shale: A Case Study of Fengcheng Formation in Mahu Sag, Junggar Basin - Jiahao Lyu; Fujie Jiang; Jing Xue; Tao Hu; Yuping Wu; Chenxi Zhang; Meiling Hu; Renda Huang (Journal of Earth Science, 2026)

Investigation of Oil Content in Lacustrine Shale-Oil Systems: Insights from Two Different Pyrolysis - Yuping Wu; Chenglin Liu; Fujie Jiang; Tao Hu; Chenxi Zhang; Jiahao Lyu; Renda Huang; Meiling Hu; Guanyun Wu; Rizwan Sarwar Awan (Journal of Earth Science, 2026)

Spatiotemporal temperature variations induced by urban extreme heat events at the micro-scale - Huifang Li; Shuman Shen; Meiling Gao; Yu Wu; Zhihua Wang; Huanfeng Shen (Urban Climate, 2026)

Bibliometric analysis of Pseudomonas aeruginosa vaccine development highlighting research status, evolution, and future opportunities - Shiqin Huang; Yi Zhou; Meiling Wu; Xinyan He; Jie Liu; Xinyao Chen; Chunyong Xia; Wen Wu; Ying Fan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Nicking-controlled biosensor: Integrating DNA Walker-RCA circuit with trimetallic nanozyme for aflatoxin B1 detection - Longsheng Jin; YuJing Liu; Wenqing Xia; Meiling Zhou; Ziying Xiao; Jingyu Ge; Xiao Yuan; Qinqiang Zhu; Meisheng Wu (Analytica Chimica Acta, 2026)

Predicting ecological risks of heavy metals in watersheds based on interpretable machine learning models: under the framework of data scarcity - Hong Chen; Meiling Kong; Zhenghua Wu; Liu Gong; Lanlan Huang; Yihan Li; Fazhi Xie (Environmental Monitoring and Assessment, 2026)

Comparative assessment of female reproductive toxicity from PFOA and its alternative GenX in mice and human granulosa cells - Yangyang Yuan; Binhui Wang; Yuyu Fan; Meiling Le; Lihai Wu; Shiyi Deng; Jian Huang; Dalei Zhang (Toxicology and Applied Pharmacology, 2026)

Divergent responses of water use efficiency to drought events in planted forests: Southern vs Northern China - Zipeng Gu; Xingwei Chen; Huaxia Yao; Jiefeng Wu; Meiling Zheng; Wenjun Gu; Senzhen Wang (Journal of Hydrology, 2026)

Cationic polyacrylamide (CPAM) assisted leaching of rare earth ore containing clay minerals by inhibiting swelling and promoting permeation of ammonium sulfate solution - Meiling Jiang; Huifang Yang; Wenqian Cui; Yunbo Yang; Zhenyue Zhang; Zhengyan He; Zhigao Xu; Ming Wu; Jun Zhao; Ruan Chi (Hydrometallurgy, 2026)

Spatiotemporal graph for detecting evolution characteristics of karst rocky desertification from long time-series Landsat images - Yanan Wen; Meiling Liu; Zeyan Wu; Qian Zhang; Jialei Su; Zijian Hu (CATENA, 2026)

Reciprocal rate-modulated evolution of slow-moving reservoir landslide: learning from hydrological-adapted block model - Shu Zhang; Qiang Li; Huiming Tang; Zongxing Zou; Jianfan Zhao; Jiefei Zhang; Meiling Wu (Landslides, 2026)

Spatiotemporal changes of soil organic carbon in intensive croplands over three decades: Emerging role of farmland utilization shifts - Mingtao Xiang; Xiaojia Chen; Songchao Chen; Chunyan Wu; Meiling Sheng; Zhouqiao Ren; Wanzhu Ma; Ming Ming; Xunfei Deng; Yu Zhan (Soil and Tillage Research, 2025)

Unveiling the seasonal variations in greenhouse gas emissions from a representative full-scale swine farm’s wastewater treatment system via life cycle assessment - Xingyun Yuan; Meiling Lu; Zhiyin Wu; Zixuan Liu; Xin Wen; Baohua Ma; Yongde Zou; Tao Chen; Yinbao Wu (Process Safety and Environmental Protection, 2025)

Monsoonal intensity dominated the Eocene evolution of paleovegetation and paleoclimate in northern South China Sea - Jinhua Zeng; Tao Jiang; Keqiang Wu; Desheng Hu; Yong Man; Licheng Cao; Cong Cheng; Zigui Chen; Kun Wang; Nan Bai; Meiling Feng; Ziyi Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Spatial accessibility to public electric vehicle charging infrastructure and multi-mechanism process of regional inequity in Greater Bay Area, China - Xing Gao; Huizi Wang; Ying Zhang; Keyu Zhai; Meiling Wu (Journal of Transport Geography, 2025)

Solar-driven superhydrophobic modified polyurethane sponge for rapid in-situ recovery of oil and microplastics in marine oil spill co-contamination - Chuanliang Zhao; Sidan Peng; Bo Wu; Le Kang; Lanlan Liang; Meiling Liu; Liwei Yang; Wendong Wang; Xing Xu (Journal of Hazardous Materials, 2025)

Manufacture of a fluorescent covalent organic framework and its Eu3 + -functionalized material for the design of dual-functional platforms for fluorescent and colorimetric sensing - Yuqiang Xiao; Jiaqi Hu; Mingyue Wang; Yue Lan; Dandan Wang; Famin Ke; Lingling Li; Minmin Wang; Leijiao Peng; Meiling Yang; Tianzhen Gao; Jianming Wu; et al. (Journal of Environmental Chemical Engineering, 2025)

Changes in soil quality and crop productivity along rice cultivation chronosequences in saline-alkali soils - Bangyan Zhang; Jinmin Wu; Xiaolong Bai; Lei Li; Meiling Lin; Xing Xu; Fengju Zhang; Bin Wang (Journal of Environmental Management, 2025)

Visible light driven highly selective oxidation of HMF coupled with H2 evolution via bimetal-doped synergism on ZnIn2S4 nanosheets - Yachen Hu; Wei Jiang; Zijun Zhang; Qinqin Jiang; Yawen Jiang; Lang Sun; Panjing Xu; Yanling Chang; Chuanqiang Wu; Ziming Fan; Meiling Wang; Zhou Chen; et al. (Chemical Engineering Journal, 2025)

The role of the casein kinase 1 (CK1) family in fungal infections - Meiling Wu; Haolin Zhang; Miao Jia; Xingyu Cao; Juan Wang (Molecular Biology Reports, 2025)

AKR1B1 is Required for Maintaining Acute Leukemia Cell Survival by Epigenetic Silencing of Tumor Suppressor Genes - Jingyu Chen; Lu Xu; Wangshi Li; Meiling Sun; Yao Chen; Ting Qiu; Yue Wu; Xingzhi Lv; Fukai Liu; Huitao Fan (Biochemical Genetics, 2025)

Deciphering macrophage heterogeneity and factors driving M2 polarization in lung adenocarcinoma through single-cell RNA sequencing - Meiling Sheng; Beiwei Yu; Qunzhi Wang; Yuanchao Xiao; Ming Ling; Xiaoming Wu (Apoptosis, 2025)

Alternating current charging-strengthened anode interface and cathode prelithiation synergistically improve comprehensive performances of LiFePO4||graphite batteries - Meiling Wu; Yulong Zhang; Shiyou Li; Lei Niu; Ningshuang Zhang; Xiaoling Cui (Chemical Engineering Journal, 2025)

Impacts of turbulent intermittency and pressure oscillation on persistent heavy haze pollution - Qianhui Li; Wei Wei; Hongsheng Zhang; Meiling Sun; Bingui Wu; Jingle Liu (Atmospheric Research, 2025)

Graft−growth of Cobalt−based Prussian blue analogs on bamboo for indoor formaldehyde removal - Yi Zhu; Honghui Yan; Ruiqi Xin; Yuding Zhu; Miaomiao Zheng; Xiangxing Wu; Yiting Zhang; Ting Wang; Meiling Chen; Song Li; Jeonghun Kim; Wenkai Zhu (Environmental Research, 2025)

Regulatory mechanism of microplastics on arsenic bioavailability in a subtropical estuary, China - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Rong Yu; Wei Yu; Binxin Wu; Meiling Xiao (Science of The Total Environment, 2025)

Different impacts of temperature and precipitation on vegetation net primary production of global marsh wetlands - Jiaqi Zhang; Meiling Zhao; Rong Ma; Mingming Feng; Chen Ding; Liyuan Wu; Xianguo Lu; Xiangjin Shen; Ming Jiang (Global and Planetary Change, 2025)

Self-assembled mogroside v nanomicelle system improves oral bioavailability of the magnolol - Chengzhi Liu; Lingyi Ren; Niu Liu; Mengchu Niu; Yifei Xiang; Xianhua Wu; Changhua Lin; Zhengmin Liang; Meiling Yu; Jiakang He (Food Chemistry, 2025)

Achieving ultralong-lived flexible room-temperature phosphorescence, detection of strain and photostability, and high-level data encryption based on benzophenone derivatives - Yang Zhu; Haoqun Wu; Meiling Pan; Lei Ma; Yongtao Wang (Chemical Engineering Journal, 2025)

Comparison of Meltpro Myco Assay with MALDI-TOF Mass Spectrometry for rapid and accurate detection of clinical Mycobacterium Species - Kehao Peng; Liuyue Xu; Xuezhi Wang; Jianming Hong; Gengchen Zhang; Yuchuan Zhao; Yinong Ye; Zengqi Huang; Jinmei Zhang; Yuchun Huang; Zhiqiao Wu; Xiaolin Yu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Large-scale mapping and uncertainty assessment of dominant tree species in southern China based on Sentinel-2 time series - Ben Yang; Yuxin Zhao; Junji Li; Meiling Liu; Lei Feng; Botian Zhou; Ling Wu (Journal of Environmental Management, 2025)

Calcium isotope composition of the Gangdese continental arc deep crust and implications for making continental crust - Meiling Wang; Zaicong Wang; Liang Guo; Zongqi Zou; Fei Wu; Wei Dai; Jingliang Guo; Kang Chen; Lanping Feng; Haihong Chen; Ming Li; Yongsheng Liu (Geochimica et Cosmochimica Acta, 2025)

Three birds with one stone: a facile superparamagnetic aptasensor for selective capture, dual-mode detection and efficient elimination of methicillin-resistant Staphylococcus aureus - Fengfeng Zhao; Yuming Yao; Shuo Ma; Jiwei Wang; Abudushalamu GuliNaizhaer; Meiling Zhou; Yaya Chen; Xun Gao; Xiaobo Fan; Chen Zhang; Xinglu Jiang; Guoqiu Wu (Chemical Engineering Journal, 2025)

Synergistic enhancement of ionic conductivity and mechanical strength of inorganic hydroxide exchange membranes via orientation engineering for water electrolysis - Qingjie Xi; Wei Wang; Ruixiang Guo; Chenyi Zhao; Xiaofen Liu; Xiaorui Jin; Yongan Yang; Kai-Ge Zhou; Meiling Wu (Chemical Engineering Journal, 2025)

Confining PMo12 in flexible nanocages for enhanced electrochemical energy storage - Yuanyuan Yan; Chongji Wang; Yuhang Chen; Cao Wu; Kezhuo Xie; Zhenyu Liu; Tianyuan Zhang; Weifeng Liu; Xuguang Liu; Tian Wang; Zhaofeng Chen; Shengbo Sang; et al. (Chemical Engineering Journal, 2025)

Hypoxia-activated and status-reversing hydrogel platform initiates potent systemic immunity against triple-negative breast cancer - Zhike Li; Xianzhou Huang; Jin Yang; Meiling Shen; Yanjie You; Qinjie Wu; Changyang Gong (Chemical Engineering Journal, 2025)

Spatiotemporal impacts of scientific and technological innovation and industry chain resilience on ecological Efficiency: Evidence from 284 Chinese cities - Meiling Wu; Wei Liu; Rongguang Zhang; Zhiran Fan; Xueyan Zhong (Journal of Environmental Management, 2025)

Development of the novel formulations of perospirone for the treatment of schizophrenia - Zijun Zhang; Famin Ke; Jili Wu; Xiyao Li; Xin Chen; Lanxing Zhang; Pei Jing; Zerong Liu; Zhongbing Liu; Ruilin Lu; Shihua Fu; Meiling Zhou; et al. (Drug Delivery and Translational Research, 2025)

Multi-residue analytical method development and dietary exposure risk assessment of 345 pesticides in mango by LC-Q-TOF/MS - Xingqiang Wu; Jianxun Li; Jing Wei; Kaixuan Tong; Yujie Xie; Qiaoying Chang; Xiaoxuan Yu; Bei Li; Meiling Lu; Chunlin Fan; Hui Chen (Food Control, 2025)

Construct favorable solid electrolyte interphase by applying alternating current discharge during battery formation - Yulong Zhang; Shiyou Li; Meiling Wu; Lijuan Wang; Ning He; Yin Quan; Peng Wang; Dongni Zhao; Xiaoling Cui (Chemical Engineering Journal, 2025)

Estimation of winter wheat yield by assimilating MODIS LAI and VIC optimized soil moisture into the WOFOST model - Jing Zhang; Guijun Yang; Junhua Kang; Dongli Wu; Zhenhong Li; Weinan Chen; Meiling Gao; Yue Yang; Aohua Tang; Yang Meng; Zhihui Wang (European Journal of Agronomy, 2025)

Autophagy in skeletal muscle dysfunction of chronic obstructive pulmonary disease: implications, mechanisms, and perspectives - Xiaoyu Han; Peijun Li; Meiling Jiang; Yuanyuan Cao; Yingqi Wang; Linhong Jiang; Xiaodan Liu; Weibing Wu (Journal of Zhejiang University-SCIENCE B, 2025)

Thresholding Dolphin Whistles Based on Signal Correlation and Impulsive Noise Features Under Stationary Wavelet Transform - Xiang Zhou; Ru Wu; Wen Chen; Meiling Dai; Peibin Zhu; Xiaomei Xu (Journal of Marine Science and Engineering, 2025)
The time–frequency characteristics of dolphin whistle signals under diverse ecological conditions and during environmental changes are key research topics that focus on the adaptive and response mechanisms of dolphins to the marine environment. To enhance the quality and utilization of passive acoustic monitoring (PAM) recorded dolphin whistles, the challenges faced by current wavelet thresholding methods in achieving precise threshold denoising under low signal-to-noise ratio (SNR) are confronted. This paper presents a thresholding denoising method based on stationary wavelet transform (SWT), utilizing suppression impulsive and autocorrelation function (SI-ACF) to select precise thresholds. This method introduces a denoising metric ρ, based on the correlation of whistle signals, which facilitates precise threshold estimation under low SNR without requiring prior information. Additionally, it exploits the high amplitude and broadband characteristics of impulsive noise, and utilizes the multi-resolution information of the wavelet domain to remove impulsive noise through a multi-level sliding window approach. The SI-ACF method was validated using both simulated and real whistle datasets. Simulated signals were employed to evaluate the method’s denoising performance under three types of typical underwater noise. Real whistles were used to confirm its applicability in real scenarios. The test results show the SI-ACF method effectively eliminates noise, improves whistle signal spectrogram visualization, and enhances the accuracy of automated whistle detection, highlighting its potential for whistle signal preprocessing under low SNR.

Facile solvothermal synthesis of ultrafine platinum nanowires on carbon nanotubes to enhance hydrogen evolution performance - Chang-An Zhou; Meiling Ran; Huixi Chen; Tingting Ma; Chunhui Wu; Hong Zhang; Lei Song; Chao Wang; Kui Ma; Hairong Yue (Fuel, 2025)

Ultrastable Ti@Ir core-shell catalyst with low iridium loading for water electrolysis at industrial-level current density - Jiahao Yang; Zhaoping Shi; Yibo Wang; Hongxiang Wu; Jing Ni; Pengbo Wang; Meiling Xiao; Changpeng Liu; Wei Xing (Chemical Engineering Journal, 2025)

Expanding the electrochemical stable window of water through propylene carbonate addition for aqueous-based energy storage devices - Meiling Tang; Yu Meng; Yibing Yang; Shuilin Wu (Chemical Engineering Journal, 2025)

Longitudinal relationship between built environment and physical fitness in Chinese children and adolescents: Findings from the COHERENCE study - Jinghong Liang; Shan Huang; Wenwen Bao; Yingqi Pu; Meiling Liu; Xiuzhi Yang; Zhuowen Wu; Jiaqi Chen; Guanghui Dong; Yajun Chen (Building and Environment, 2025)

Paleoenvironmental evolution and East Asian monsoon records through three stages of paleochannels since the mid-pleistocene in the Western Bohai Sea, North China - Shuyu Wu; Jun Liu; Hongxian Chu; Yongcai Feng; Meiling Yin; Lixin Pei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Fermentation by Penicillium polonicum improves the functional components and biological effects of orange peel via producing β-glucosidase without the risk of potential mycotoxins - Yan Liang; Chunling Lai; Liangliang Gao; Qingna Wu; Meiling Huang; Yueming Jiang; Jun Zhang (Food Bioscience, 2024)

Exposure to butylparaben induces oxidative stress and apoptosis in the liver of Polypedates megacephalus tadpole - Xiaoqi Ai; Muhammad Shahid Iqbal; Rui Lin; Xia Wu; Lijun Wang; Meiling Hong (Frontiers in Marine Science, 2024)
Butylparaben (BuP) is a ubiquitous preservative in cosmetics, foods, and medicine. As an emerging pollutant, it has gained wide attention in recent years. Because amphibians have both aquatic and terrestrial life stages and high skin permeability, they are sensitive to environmental changes. To assess the toxic effects of BuP on amphibians, the present study was conducted on the spot-legged tree frog ( Polypedates megacephalus ) tadpoles. In the present study, LC 50 of BuP for 96 h exposures was 3509 µg/L. Then, the tadpoles were exposed to 0, 350 and 2100 µg/L BuP (hereafter named as CK, B1 and B2) for 12, 24 and 48 h, the oxidative stress and apoptosis in the liver were analyzed. The results showed that the content of MDA and activity of SOD and GSH-PX were increased with an increase in BuP exposure. BuP stress significantly altered the expression of Nrf2-Keap1 signal pathway genes. An increase in the expression of JAK-STAT signal pathway genes was observed with an increase in the exposure to BuP concentration at 24 and 48 h. In contrast, the expression of negative regulators of JAK-STAT signal pathway were significantly increased at 12 h and decreased at 24 and 48 h. A significant decrease in pro-apoptosis genes expression ( Bax and Caspase3 ) were observed at 12 h but increased at 24 and 48 h, while the expression of anti-apoptosis gene ( Bcl-2 ) decreased at 24 and 48 h. These results provide a valuable reference point for assessing the ecological and health risks associated with BuP in the environment.

Surface phosphorylated Li5FeO4 prelithiation additive synergistically improves the air-stability and lithium-ion conductivity - Lei Niu; Meiling Wu; Yulong Zhang; Cankun Gao; Xin Li; Hao Ding; Ning He; Peng Wang; Jiawen Zhang; Jingxuan Yan; Ningshuang Zhang; Dongni Zhao; et al. (Chemical Engineering Journal, 2024)

Integrated effect of aspect ratio and tree spacing on pedestrian thermal comfort of street canyon - Xiaoping Chen; Meng Han; Jinyu He; Hang Ma; Meiling Han; Yanhong Liu; Xiaogang Wu (International Journal of Biometeorology, 2024)

Designing a multi-level reverse logistics network for waste batteries of electric vehicles under uncertainty—A case study in the Yangtze River Delta Urban Agglomerations of China - Meiling He; Qipeng Li; Xiaohui Wu; Kazuhiro Izui (Journal of Cleaner Production, 2024)

Nanoarchitectonics of bamboo-based heterojunction photocatalyst for effective removal of organic pollutants - Xiaole Yan; Meiling Chen; Junning Wang; Zhaodong Wang; Ruiqi Xin; Dujuan Wu; Ye Song; Song Li; Wenkai Zhu; Chaohai Wang; Yanli Mao (Chemical Engineering Journal, 2024)

A Profile of Drug-Resistant Mutations in Mycobacterium tuberculosis Isolates from Guangdong Province, China - Chenchen Zhang; Zhuhua Wu; Xinchun Huang; Yuchuan Zhao; Qi Sun; Yanmei Chen; Huixin Guo; Qinghua Liao; Huizhong Wu; Xunxun Chen; Anqi Liang; Wenya Dong; et al. (Indian Journal of Microbiology, 2024)

Post-productivism and rural revitalization in China: Drivers and outcomes - Meiling Wu; Qian Forrest Zhang; John Donaldson (Journal of Rural Studies, 2024)

Spatiotemporal variations of plankton communities in different water bodies of the Yellow River: Structural characteristics, biogeographic patterns, environmental responses, and community assembly - Meiling Yi; Lingqi Li; Haoran Li; Chang Liu; Ya Deng; Zi Wu; Yang Li (Journal of Hydrology, 2024)

A novel multi-level reverse logistics network design optimization model for waste batteries considering facility technology types - Meiling He; Qipeng Li; Xiaohui Wu; Xun Han (Journal of Cleaner Production, 2024)

Adsorption Performance of Chitosan and Glutaraldehyde Modified Biochars for Trivalent Antimony in Acidic Wastewater - Huifang Lei; Nora F. Y. Tam; Xinhua Geng; Meiling Zhong; Xiaolan Lao; Xiaotong Su; Xuexia Huang; Lezhang Wei; Yu Liu; Qihang Wu; Ying-heng Fei; Dinggui Luo; et al. (Water, Air, & Soil Pollution, 2024)

Elevated CO2 exacerbates the risk of methylmercury exposure in consuming aquatic products: Evidence from a complex paddy wetland ecosystem - Danni Wu; Lei Chen; Xueying Zong; Fan Jiang; Xiaojie Wang; Meiling Xu; Fuxun Ai; Wenchao Du; Ying Yin; Hongyan Guo (Environmental Pollution, 2024)

Calcium polypeptide mitigates Cd toxicity in rice via reducing oxidative stress and regulating pectin modification - Hongbing Chen; Xiaojun Tang; Tiejun Wang; Weifang Liao; Zhixian Wu; Meiling Wu; Zhihao Song; Yadong Li; Pan Luo (Plant Cell Reports, 2024)

Subchronic co-exposure of polystyrene nanoplastics and 3-BHA significantly aggravated the reproductive toxicity of ovaries and uterus in female mice - Guanghua Xiong; Haiyan Zhang; Yulin Peng; Huangqi Shi; Meiling Han; Tianle Hu; Hongcheng Wang; Shangrong Zhang; Xiaoqing Wu; Gaoxiao Xu; Jun'e Zhang; Yong Liu (Environmental Pollution, 2024)

Validation of endogenous U6 promoters for expanding the CRISPR toolbox in Nicotiana tabacum - Pan Luo; Siyuan Li; Lulu Li; Yanyan Li; Ying Qiao; Xianzhi Wu; Meiling Wu; Zhihao Song; Yong Yang; Ji Feng; Xingchun Tang (In Vitro Cellular & Developmental Biology - Plant, 2024)

STAT2 negatively regulates RIG-I in the antiviral innate immunity of black carp - Ji Liu; Chushan Dai; Lijun Yin; Xiao Yang; Jun Yan; Meiling Liu; Hui Wu; Jun Xiao; Weiguang Kong; Zhen Xu; Hao Feng (Fish & Shellfish Immunology, 2024)

Resting-state EEG Microstate Features Can Quantitatively Predict Autistic Traits in Typically Developing Individuals - Huibin Jia; Xiangci Wu; Xiaolin Zhang; Meiling Guo; Chunying Yang; Enguo Wang (Brain Topography, 2024)

Identification of dynamic changes in volatile compounds and metabolites during the smoking process of Zhenba bacon by GC-IMS combined metabolomics - Shuai Han; Meiling Ke; Ling Wang; Haidong Ma; Guofei Wu; Lianxu Zhu; Tao Zhang; Hongzhao Lu (Food Research International, 2024)

Synchronized achieving amount reduction and efficiency increase of lithium salt-type additive by alternating current pulse discharge technology - Shiyou Li; Yulong Zhang; Shumin Wu; Yin Quan; Meiling Wu; Peng Wang; Dongni Zhao; Xiaoling Cui (Chemical Engineering Journal, 2024)

Utilizing different types of biomass materials to modify steel slag for the preparation of composite materials used in the adsorption and solidification of Pb in solutions and soil - An Wang; Meiling Wu; Zhongyuan Li; Yuqiang Zhou; Fanmin Zhu; Zhanbin Huang (Science of The Total Environment, 2024)

Effects of butyl paraben on behavior and molecular mechanism of Chinese striped-necked turtle (Mauremys sinensis) - Xia Wu; Ijaz Khan; Xiaoqi Ai; Jiliang Zhang; Haitao Shi; Ding Li; Meiling Hong (Aquatic Toxicology, 2024)

Identification of QTLs associated with very-long chain fatty acid (VLCFA) content via linkage mapping and BSA-seq in peanut - Xiaomeng Xue; Jianguo Li; Jie Wu; Meiling Hu; Nian Liu; Liying Yan; Yuning Chen; Xin Wang; Yanping Kang; Zhihui Wang; Huifang Jiang; Yong Lei; et al. (Theoretical and Applied Genetics, 2024)

One-step synthesis of color-tunable carbon dots-based organic long persistent luminescence materials - Yujie Di; Weifeng Liu; Shuhao Shi; Tao Wu; Meiling Wang; Xuguang Liu (Chemical Engineering Journal, 2024)

Black carp LGP2 suppresses RIG-I mediated IFN signaling during the antiviral innate immunity - Yixuan He; Ji Liu; Yujia Miao; Meiling Liu; Hui Wu; Jun Xiao; Hao Feng (Fish & Shellfish Immunology, 2023)

Bilobetin attenuates Staphylococcus aureus virulence by targeting Von Willebrand factor-binding protein and staphylocoagulase - Chongling Zhang; Wenyuan Zhang; Shuyue Zhu; Chunjie Hu; Sihua Che; Meiling Wang; Mengli Jin; Nan Bian; Wu Song; Shuang Jiang; Yijing Jiang; Juan Hou; et al. (World Journal of Microbiology and Biotechnology, 2023)

Nanocomposite hydrogel to deliver the immunomodulator lenalidomide and anti-inflammatory hesperidin locally to joints affected by rheumatoid arthritis - Xingjie Du; Yan Lin; Zheyu Shuai; Junfeng Duan; Changguang Wang; Junsheng Liu; Jun Jiang; Jianming Wu; Meiling Zhou; Zhirong Zhang; Zhongbing Liu; Xiangyu Zhou; et al. (Chemical Engineering Journal, 2023)

Experimental and mechanistic study on the removal of lead from solution by sulfuric acid modified steel slag adsorbent - An Wang; Meiling Wu; Zhongyuan Li; Yuqiang Zhou; Zhanbin Huang (Journal of Environmental Chemical Engineering, 2023)

Study on the effect of KMnO4−modified humic acid residues on the removal of Hg(Ⅱ)/Pb(Ⅱ) from solution - Yingnan Wang; Lingjian Kong; Meiling Wu; Haoran Ma; Zhanbin Huang (Journal of Environmental Chemical Engineering, 2023)

Dorsal and ventral fronto-amygdala networks underlie risky decision-making in age-related cognitive decline - Ping Ren; Manxiu Ma; Yuchuan Zhuang; Jiayin Huang; Meiling Tan; Donghui Wu; Guozhi Luo (GeroScience, 2023)
Older adults often have difficulty in making decisions under uncertainty, increasing the risk of financial exploitation. However, it is still under investigation about the extent to which cognitive decline influences risky decision-making and the underlying neural correlates. We hypothesized that the individual differences of risk-taking behavior depend on cognitive integrity, in which the dorsal and ventral fronto-amygdala connectivity would play dissociable roles. In the current study, thirty-six young and 51 older adults were tested with the Iowa gambling task combing resting-state and task-related functional magnetic resonance imaging. The results showed significant changes in behaviors and the fronto-amygdala network in older adults relative to young adults. More importantly, age-effect on risk-taking behaviors was remarkably different in cognitively normal and impaired older adults. In resting-state analysis, task performance was positively correlated with the ventral fronto-amygdala connectivity and negatively correlated with the dorsal fronto-amygdala connectivity in cognitively impaired older adults, compared with cognitively normal individuals. Furthermore, task-related analysis confirmed the relationships between dorsal/ventral fronto-amygdala network and risk-taking behaviors depending on cognitive integrity. These findings indicate that the fronto-amygdala network is crucial for understanding altered risky decision-making in aging, suggesting dissociable contributions of the dorsal and ventral pathways in the context of cognitive decline.

Baicalein ameliorates polymyxin B-induced acute renal injury by inhibiting ferroptosis via regulation of SIRT1/p53 acetylation - Meiling Yu; Hongyu Li; Boying Wang; Zhenxiang Wu; Sheng Wu; Guojun Jiang; Huaxue Wang; Yingying Huang (Chemico-Biological Interactions, 2023)

Oil occurrence state and quantity in alkaline lacustrine shale using a high-frequency NMR technique - Chenxi Zhang; Fujie Jiang; Tao Hu; Di Chen; Liliang Huang; Zhenxue Jiang; Xiaohao Wang; Zheyu Liu; Yuping Wu; Jiahao Lv; Renda Huang; Meiling Hu; et al. (Marine and Petroleum Geology, 2023)

High mechanical CuO@stainless steel mesh for continuous and durable separation of surfactant-stabilized viscous and light/heavy-mixed oily emulsions in liter-scale - Qing He; Meiling Guo; Juan Shu; Hua Hu; Hongwei Su; Guilong Yan; Zhenyu Li; Li Wang; Dong Xiang; Chunxia Zhao; Yuanpeng Wu; Wei Wang; et al. (Journal of Water Process Engineering, 2023)

Involvement of CD27 in innate and adaptive immunities of Nile tilapia (Oreochromis niloticus) - Baijian Jiang; Qi Li; Zhiqiang Zhang; Yongxiong Huang; Yiqin Wu; Xing Li; Meiling Huang; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

SUMO and PIAS repress NF-κB activation in a basal chordate - Shenghui Chen; Xianan Fu; Ruihua Wang; Mingshi Li; Xinyu Yan; Zirui Yue; Shang-Wu Chen; Meiling Dong; Anlong Xu; Shengfeng Huang (Fish & Shellfish Immunology, 2023)

An injectable antibacterial hydrogel to regulate ocular immune for endophthalmitis treatment - Zunzhen Ming; Lin Han; Huanhuan Zhu; Meiyu Bao; Qiangyuan Fan; Shaobo Xue; Kesheng Wang; Yue Zhang; Meiling Lu; Chongshun Xu; Qi Wu; Tingting Li; et al. (Chemical Engineering Journal, 2023)

Ferroptosis is involved in polymyxin B-induced acute kidney injury via activation of p53 - Hongyu Li; Boying Wang; Sheng Wu; Shuying Dong; Guojun Jiang; Yingying Huang; Xuhui Tong; Meiling Yu (Chemico-Biological Interactions, 2023)

Catalytic destruction of chlorobenzene over K-OMS-2: Inhibition of high toxic byproducts via phosphate modification - Yunpeng Long; Jiajia Liu; Meiling Chen; Renna Li; Xiaole Weng; Zhongbiao Wu (Journal of Environmental Sciences, 2023)

Molecular characterization and functional analysis of CD209E from Nile Tilapia (Oreochromis Niloticus) involved in immune response to bacterial infection - Yiqin Wu; Meiling Huang; Yishan Lu; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Astrochronology and carbon-isotope stratigraphy of the Fengcheng Formation, Junggar Basin: Terrestrial evidence for the Carboniferous-Permian Boundary - Renda Huang; Fujie Jiang; Di Chen; Ruoyuan Qiu; Tao Hu; Linhao Fang; Meiling Hu; Guanyun Wu; Chenxi Zhang; Jiahao Lv; Yuping Wu; Liliang Huang (Gondwana Research, 2023)

A Quad-Functional On-demand released nanomissile achieves cascade amplification therapy of Triple-Negative breast cancer through reversing multiple resistance - Yan Wang; Xianzhou Huang; Shunyao Zhu; Lu Li; Jin Yang; Jie Li; Li Wang; Shuang Ma; Meiling Shen; Qinjie Wu; Changyang Gong (Chemical Engineering Journal, 2023)

Evidence Supporting That C-to-U RNA Editing Is the Major Force That Drives SARS-CoV-2 Evolution - Jinxiang Wang; Liqun Wu; Xiaoxin Pu; Baoyi Liu; Meiling Cao (Journal of Molecular Evolution, 2023)

Negatively regulation of MAVS-mediated antiviral innate immune response by E3 ligase RNF5 in black carp - Jun Yan; Guoxia Qiao; Enhui Wang; Yuqing Peng; Jiamin Yu; Hui Wu; Meiling Liu; Jiagang Tu; Yongan Zhang; Hao Feng (Fish & Shellfish Immunology, 2023)

Impaired barrier integrity of endothelial cells induced by PEGylated black phosphorus nanosheets - Jiayan Chen; Weiwei Huan; Lijuan Mao; Meiling Huang; Yiqu Wu; Shulin Zhuang; Shixuan Cui (Science of The Total Environment, 2023)

Vertical profile of PCDD/Fs in soil and sediment around an abandoned e-waste dismantling site - Xiaotong Su; Yucheng Zhang; Nora F. Y. Tam; Xiaolan Lao; Meiling Zhong; Qihang Wu; Yingheng Fei; Huifang Lei; Zihui Chen; Bixian Mai; Laiguo Chen (Journal of Soils and Sediments, 2023)

Elevated CO2 exacerbates effects of TiO2 nanoparticles on rice (Oryza sativa L.) leaf transcriptome and soil bacteria - Wenqian Ma; Wenchao Du; Kaihua Gu; Meiling Xu; Ying Yin; Yuanyuan Sun; Jichun Wu; Jianguo Zhu; Hongyan Guo (Science of The Total Environment, 2023)

Partial substitution of manure reduces nitrous oxide emission with maintained yield in a winter wheat crop - Huizhou Gao; Yajing Xi; Xueping Wu; Xuexia Pei; Guopeng Liang; Ju Bai; Xiaojun Song; Meiling Zhang; Xiaotong Liu; Zixuan Han; Gang Zhao; Shengping Li (Journal of Environmental Management, 2023)

A colloidal aqueous electrolyte modulated by oleic acid for durable zinc metal anode - Meiling Wang; Xiaoyu Wu; Di Yang; Hainan Zhao; Li He; Jiaran Su; Xu Zhang; Xiuxiu Yin; Kangning Zhao; Yizhan Wang; Yingjin Wei (Chemical Engineering Journal, 2023)

SnoRNP is essential for thermospermine-mediated development in Arabidopsis thaliana - Xilong Li; Zongyun Yan; Meiling Zhang; Jiayin Wang; Peiyong Xin; Shujing Cheng; Liquan Kou; Xiaoting Zhang; Songlin Wu; Jinfang Chu; Chengqi Yi; Keqiong Ye; et al. (Science China Life Sciences, 2023)

Plant Growth Regulators Enhance Saline–Alkali Tolerance by Upregulating the Levels of Antioxidants and Osmolytes in Soybean Seedlings - Minglong Yu; Qiong Wu; Dianfeng Zheng; Naijie Feng; Xilong Liang; Meiling Liu; Yao Li; Baomin Mou (Journal of Plant Growth Regulation, 2022)

The Sponge Interaction Between Circular RNA and microRNA Serves as a Fast-Evolving Mechanism That Suppresses Non-small Cell Lung Cancer (NSCLC) in Humans - Liqun Wu; Meiling Cao; Xiaoxin Pu; Baoyi Liu; Jinxiang Wang (Journal of Molecular Evolution, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Development and characterization of novel chloroplast microsatellite markers for Cryptomeria japonica var. sinensis (Cupressaceae) and their cross-species amplification - Minqiu Wang; Meiling Yuan; Xinyu Li; Xingtong Wu; Saneyoshi Ueno; Mengying Cai; Yoshihiko Tsumura; Yafeng Wen (Biologia, 2022)

Role of gibberellin and its three GID1 receptors in Jasminum sambac stem elongation and flowering - Hongliang Zhang; Wei Wang; Jinfeng Huang; Yuting Wang; Li Hu; Yuan Yuan; Meiling Lyu; Binghua Wu (Planta, 2022)

Ternary catalyst Mn-Fe-Ce/Al2O3 for the ozonation of phenol pollutant: performance and mechanism - Manning Zhang; Dulin Yin; Jinjin Guo; Huanghe Wu; Meiling Gong; Xiangdong Feng (Environmental Science and Pollution Research, 2021)

The Effect of Composting on the Multiple Heavy Metals in the River Sediment Investigated by Multivariate Analysis - Yaoning Chen; Yanrong Chen; Yuanping Li; Yihuan Liu; Daoli Zhang; Yanxin Wu; Hui Li; Fangting Xu; Meiling Li (Water, Air, & Soil Pollution, 2021)

The complete mitochondrial genome of the hybrid grouper Epinephelus moara (♀)×Epinephelus tukula (♂), and phylogenetic analysis in subfamily Epinephelinae - Zhentong Li; Yongsheng Tian; Meiling Cheng; Linna Wang; Jingjing Zhang; Yuping Wu; Zunfang Pang; Wenhui Ma; Jieming Zhai (Acta Oceanologica Sinica, 2020)

Brain Dicer1 Is Down-Regulated in a Mouse Model of Alzheimer’s Disease Via Aβ42-Induced Repression of Nuclear Factor Erythroid 2-Related Factor 2 - Yan Wang; Meiling Lian; Jing Zhou; Shengzhou Wu (Molecular Neurobiology, 2020)

Discovery and characterization of a stable lipase with preference toward long-chain fatty acids - Meiling Chen; Xiuzhen Gao; Wu Yang; Caili Sun; Junhuan Yang; Huaiyuan Zhang; Yuanda Song (Biotechnology Letters, 2020)

Combination of NAD+ and NADPH Offers Greater Neuroprotection in Ischemic Stroke Models by Relieving Metabolic Stress - Qiao Huang; Meiling Sun; Mei Li; Dingmei Zhang; Feng Han; Jun Chao Wu; Kohji Fukunaga; Zhong Chen; Zheng-Hong Qin (Molecular Neurobiology, 2018)

Akt Inhibitor Perifosine Prevents Epileptogenesis in a Rat Model of Temporal Lobe Epilepsy - Feng Zhu; Jiejing Kai; Linglin Chen; Meiling Wu; Jingyin Dong; Qingmei Wang; Ling-Hui Zeng (Neuroscience Bulletin, 2018)

Identification and expression analysis of microRNAs during ovule development in rice (Oryza sativa) by deep sequencing - Ya Wu; Liyu Yang; Meiling Yu; Jianbo Wang (Plant Cell Reports, 2017)

Structure and geochronology of the Tongbai complex and their implications for the evolution of the Tongbai orogenic belt, central China - Huan Liu; Shoufa Lin; Chuanzhong Song; Meiling Wu (International Geology Review, 2017)

Allelism analysis of BrRfp locus in different restorer lines and map-based cloning of a fertility restorer gene, BrRfp1, for pol CMS in Chinese cabbage (Brassica rapa L.) - Huamin Zhang; Junqing Wu; Zihui Dai; Meiling Qin; Lingyu Hao; Yanjing Ren; Qingfei Li; Lugang Zhang (Theoretical and Applied Genetics, 2017)

Accumulation of intact sulfur mustard in adipose tissue and toxicokinetics by chemical conversion and isotope-dilution liquid chromatography–tandem mass spectrometry - Bin Xu; Cheng Zong; Yajiao Zhang; Tianhong Zhang; Xiaoying Wang; Meiling Qi; Jianfeng Wu; Lei Guo; Peng Wang; Jia Chen; Qin Liu; Hua Xu; et al. (Archives of Toxicology, 2017)

Genome-wide transcriptome analysis of female-sterile rice ovule shed light on its abortive mechanism - Liyu Yang; Ya Wu; Meiling Yu; Bigang Mao; Bingran Zhao; Jianbo Wang (Planta, 2016)

Decreased TK activity alters growth, yield and tolerance to low temperature and low light intensity in transgenic cucumber plants - Huangai Bi; Xubing Dong; Guoxiu Wu; Meiling Wang; Xizhen Ai (Plant Cell Reports, 2015)

Is the Hypoglycemic Action of Vanadium Compounds Related to the Suppression of Feeding? - Meiling Huang; Yaling Wu; Na Wang; Ziwei Wang; Pan Zhao; Xiaoda Yang (Biological Trace Element Research, 2014)

Vanadyl acetylacetonate upregulates PPARγ and adiponectin expression in differentiated rat adipocytes - Yaling Wu; Meiling Huang; Pan Zhao; Xiaoda Yang (JBIC Journal of Biological Inorganic Chemistry, 2013)

Effect of trichostatin A and 5-Aza-2′-deoxycytidine on transgene reactivation and epigenetic modification in transgenic pig fibroblast cells - Qingran Kong; Meiling Wu; Zhenkun Wang; Xinmiao Zhang; Lu Li; Xiangyu Liu; Yanshuang Mu; Zhonghua Liu (Molecular and Cellular Biochemistry, 2011)

Pc4, a putative movement protein of Rice stripe virus, interacts with a type I DnaJ protein and a small Hsp of rice - Lianming Lu; Zhenguo Du; Meiling Qin; Ping Wang; Hanhong Lan; Xiaoqing Niu; Dongsheng Jia; Liyan Xie; Qiying Lin; Lianhui Xie; Zujian Wu (Virus Genes, 2009)

Purification and Characterization of Two Novel Antimicrobial Peptides Subpeptin JM4-A and Subpeptin JM4-B Produced by Bacillus subtilis JM4 - Shimei Wu; Shifang Jia; Dandan Sun; Meiling Chen; Xiuzhu Chen; Jin Zhong; Liandong Huan (Current Microbiology, 2005)